(untitled) (Journal of Foreign Language Studies, 2022)
This paper identifies several language levels and registers used by Marcel Pagnol to determine the character identity and characteristics of communication situations in the novel "L’Eau des collines" published in 1988. The results show that the writer used dialect to portray local characters, and at the same time, to place the communication situations in the context of a rural area in France. Formal register used by the writer in the characters’ speeches helped demonstrate the identity of an educated person while informal register helped identify the character as a commoner. In Pagnol’s work, the opposition between formal register and informal register in the same communication situation also shows the opposition in the characters’ thinking or attitudes. Such situation is difficult to ease as each person expresses themselves in their own style.